Dalit Cinema. Issue 3 (3rd July 2018) - Yengde, Suraj
ABSTRACT: This article offers introductory remarks on the position of the Dalit in Indian cinema. It starts with the observation that the Indian film industry is an inherently caste-based, biased, mechanised product of technological industrialisation in which Dalit inclusion is not a moral concern. The mainstream film industry in India delivers the desires and principles of market and society by excluding a Dalit framework outright—a problem now being addressed by the entry of an explicitly Dalit cinema. By briefly looking at two films, Fandry (2013) and Sairat (2016), both written and directed by Dalit film-maker Nagraj Manjule, I offer a critical reading of 'Dalit Cinema'. Taking the work of Manjule, a maverick film-maker who is establishing a new discourse of Dalit-centred socio-culturism, I demonstrate the extent to which caste narratives are absent in the Indian film industry.